Long-term career attainments of deaf and hard of hearing college graduates: results from a 15-year follow-up survey. - Schroedel JG; Geyer PD (American Annals of the Deaf, 2000)
This article reports on the results of a national longitudinal survey of 240 college graduates with hearing loss. Results confirm that economic benefits resulted from these alumni's postsecondary training. Most respondents were relatively successfully employed and satisfied with life. Over time, increasing numbers had completed higher degrees and secured white-collar positions. Between 1988 and 1998, men in the study sample made more consistent earnings gains than their female counterparts. Larger proportions of deaf alumni had earned advanced degrees and secured white-collar jobs than hard of hearing alumni. Deaf alumni also earned more. Results also showed that recipients of associate's degrees earned more than recipients of bachelor's degrees. Implications of the findings for secondary educators, vocational rehabilitation counselors, and postsecondary service providers are discussed. Recommendations are made on how to improve career decision making by deaf and hard of hearing adolescents, enrich the career potential of deaf and hard of hearing women, and increase the productivity of workers with hearing loss.